THE EFFECT OF FACILITIES AND SERVICE QUALITY ON VISITOR SATISFACTION AT MOG MALL, MALANG CITY - Wulandari, Chofifah Laila; Dhakirah, Sanita; Budiarti, Lina (Jurnal Manajemen, 2026)
Abstract: The rapid development of the service sector has led to the emergence of various modern shopping centers, including the MOG Mall in Malang City, which is one of the malls with the highest number of visitors and reviews. However, some facilities are still considered inadequate by visitors. MOG Mall in Malang City is the object of this study, which aims to analyze the influence of facilities and service quality on visitor satisfaction. 100 respondents were randomly selected using a purposive sampling technique, and quantitative research methods were applied along with explanatory research methods. Data analysis was conducted using multiple linear regression, including partial and simultaneous hypothesis testing. The study findings show that visitor satisfaction is positively and significantly influenced by high-quality facilities and services. Therefore, improving comfortable facilities and responsive service needs to be a priority to increase visitor satisfaction.Keywords: Facilities, Service Quality, Visitor Satisfaction